Developing Interactive E-Module to Enhancing Mathematical Problem-Solving Ability through Computational Thinking - Putra, Komang Hendri Nugraha; Suparta, I Nengah; Sudiarta, I Gst. Putu (Darul Yasin Al Sys, 2025)
This study aims to develop an interactive e-module oriented towards computational thinking to enhance the problem-solving skills of 10th-grade high school students in the topic of number sequences and series. The e-module was developed using the Plomp model, which consists of four stages: preliminary investigation, design, realization/construction, and test, evaluation, and revision. The e-module was developed using the Moodle platform with integration of H5P features and Scratch. The research was conducted at SMA Negeri 1 Singaraja, involving three 10th-grade science classes. Research instruments included validation sheets, student and teacher response questionnaires, and a problem-solving ability test. The results show that the developed e-module met the validity criteria with an average score of 3.7 based on expert assessment. The e-module also met the practicality criteria with an average student response score of 4.56 and teacher response score of 4.71. The effectiveness of the e-module was demonstrated through a significant improvement in students' problem-solving abilities (p-value = 2.8293e-6 < 0.05) with a large effect size (Cohen's d = |-1.23537|). In conclusion, the developed interactive e-module oriented towards computational thinking is valid, practical, and effective in improving students' mathematical problem-solving skills in the topic of number sequences and series.